Funding Community Colleges in Nepal: Issues and Mitigation Measures - Gupta, Shatrughan Prasad (Shiksha Shastra Saurabh, 2022)
The regular development grants provided by the University Grants Commission (UGC) to community colleges are the most important financial support to them. UGC is also supporting its faculties and students through fellowship and scholarship schemes which are another milestone to foster the mission of community colleges. Besides, local governments, individuals, student fees, donations, alumnae support, and income from religious works are also sources of funding. These qualitative and empirical methods based on secondary sources with the eyes of social justice theory in education aim to investigate the funding modality of UGC and its impact on access to higher education. It also aims to point out some of the problems, and issues and highlight the implications of funding, in the Nepalese context. It was found that the input-based funding modality which was based on the indicators such as several students, location, programs, pass rate, and many more was insufficient to promote the access, quality, and relevancy of higher education in community colleges in Nepal.